George Back (1796-1878) - Neatby, L.H. (ARCTIC, 1983)
George Back, British admiral and arctic explorer, was born in 1796 and joined the Navy in 1808. At the age of thirteen he was wounded, made a prisoner of war, and lodged in the French fortress of Verdun. He passed several years of captivity by devoting himself to the study of drawing and mathematics. Returning to the Navy in 1818, Back sailed as mate in the Trent, under Lieutenant John Franklin, on an abortive voyage into the Spitsbergen ice. In the following year, his qualifications as artist procured him an appointment on Franklin's first overland expedition to the Polar Sea (1819-1822). . The courage and endurance displayed by Back at that time was a greater service to discovery than any of the later expeditions made under his own command: he saved the lives of Franklin and his surgeon-scientist John Richardson and so preserved the priceless geographical and scientific data gathered by the expedition. Between 1825 and 1827, Back was second-in-command of Franklin's second overland expedition. The lessons of the costly previous journey had been well learned; with minimum hardships and casualties, the map of the North American Arctic was vastly extended. Nearly half of a previously unknown shoreline was laid down by the two expeditions. . In the years of 1836-37, Back commanded H.M.S. Terror on a cruise into northern Hudson Bay. The ship was beset and drifted for months in bitter cold, heaved up on a mound of ice. When this frozen platform collapsed, the ship was nearly capsized into the waters of the bay, but she escaped with numerous leaks and a badly wrenched keel to reach a home port. . In Back, the "gentleman" predominated over the "officer". He managed his Fish River boat crew with tact, but he exasperated the factors of the fur trade - who professed to be his equals and whom he ought to have made a point of conciliating - by his conceit and patronizing airs. On the other hand, his aptitude for dialects permitted him to fraternize with Metis, Indian, and Eskimo: he relished posing as a "great chief". But ...